Imbalance Learning Using Heterogeneous Ensembles - Zefrehi, Hossein Ghaderi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In pattern classification, class-imbalance problem occurs when the number of samples in one of the classes is much larger than those in the others. In such cases, the performance of classifiers is generally poor on the minority class. Ensembles of classifiers are used to tackle this problem where each member is developed using a different balanced dataset. In this approach, one balancing strategy and a classifier prototype is generally used. In order to increase the diversity among the members, bagging and boosting are also considered. In this thesis, the use of heterogeneous ensembles utilizing multiple prototypes and multiple balancing schemes for imbalance learning is addressed. Experiments conducted on 66 datasets have shown that significant improvements can be achieved by employing multiple prototypes. It is also observed that multiple balancing schemes contribute to the performance scores, especially in simple and bagging-based ensembles.

ÖZ: Örüntü tanımada, bir sınıftaki örnek sayısı diğer sınıflarınkinden çok daha fazla olduğunda sınıf-denksizliği problem oluşmaktadır. Bu tür durumlarda, sınıflandırıcı başarımı kıüçük sınflarda düşük olmaktadır. Bu problemi aşmak için, her üyenin denkleştirilmiş bir veri kümesi ile eğitildiği çoğul sınıflandırıcılı sistemler kullanılmaktadır. Bu sistemler, genellikle bir denkleştirme ve bir sınıflandırıcı tipi ile geliştirilmektedir. Sınıflandırıcılar arasındaki farklılıkları artırmak için, torbalama ve artırma teknikleri de kullanılmaktadır. Bu tezde, birden fazla denkleştirme ve sınıflandırcı tipi kullanan heterojen çoğul sınıflandırıcı sistemlerin denksizlik öğrenmede kullanımı çalışılmıştır. 66 veri kümesinde yapılan deneysel çalışmalar, birden fazla sınıflandırıcı tipi kullanılarak başarımda belirgin iyileştirmeler sağlanabileceğini göstermiştir. Ayrıca, birden fazla denkleştirme algoritmasının kullanılmasının, özellikle basit ve torbalama-tabanlı sistemlerin başarımına katkıda bulunduğu gözlemlenmiştir.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2018. Supervisor: Prof. Dr. Hakan Altınçay.
Keywords: Computer Engineering; Machine learning--Artificial intelligence - Data processing; Imbalance learning; classifier ensembles; bagging; boosting; heterogeneous ensembles; multi-balancing